Platelet-Rich Fibrin (PRF) Analyzed for Cytokine Profiles - A Misguided Hope for Osteogenesis in Jawbone Defects? Research and Clinical Observational Study - Lechner J; vonBaehr V; Doebis C; Notter F; Schick F (Dove Medical Press, 2024)
Johann Lechner,1 Volker vonBaehr,2 Cornelia Doebis,3 Florian Notter,4 Fabian Schick4 1Department of Osteoimmunology, Clinic for Integrative Dentistry, Munich, Germany; 2Department of Immunology and Allergology, Institute for Medical Diagnostics, Berlin, Germany; 3Department of Analysis, Institute for Medical Diagnostics, Berlin, Germany; 4Department of Implantology, Clinic for Integrative Dentistry, Munich, GermanyCorrespondence: Johann Lechner, Department of Osteoimmunology, Clinic for Integrative Dentistry, Gruenwalder Str. 10A, Munich, 81547, Germany, Tel +49 89 697 0129, Fax +49 89 692 5830, Email drlechner@aol.comBackground: Platelet-rich fibrin (PRF) blood concentrates are used in oral implantology and defect surgery to promote osteoneogenesis in Bone Marrow Defects in Jawbone (BMDJ), according to the morphology of fatty-degenerative osteonecrosis also called FDOJ.Question: Can the benefit of PRF on alveolar osteoneogenesis be confirmed by cytokine analysis?.Methods: The cytokine expressions of the PRF samples in 26 patients undergoing BMDJ/FDOJ surgery in the same session were analysed for seven cytokines (RANTES/CCL5; FGF-2; IL-1RA; Il-6; IL-8; MCP-1; TNF-a) by multiplex (Luminex). The FDOJ samples of these 26 BMDJ/FDOJ patients were analysed for the RANTES/CCL5 expression only.Results: Cytokine expression in PRF is compared to reference values for healthy medullary bone of the jaw and BMDJ/FDOJ and shows that the cytokine expressions of the PRF samples do not compensate or counteract prima vista for the cytokine dysregulations present in the BMDJ/FDOJ areas.Discussion: To define the aid of cytokines studied in PRF in the restoration of the immunological dysregulation in areas of BMDJ/FDOJ, literature is reviewed comparing RANTES/CCL5, IL-1ra, TNF-α and MCP-1/CCL2 expression in PRF and BMDJ/FDOJ. Immunoregulatory properties of PRF in alveolar bone restoration are evaluated.Summary: PRF was mistakenly thought to be a cure for bone healing, which is here shown to be incorrect. Enoral Ultrasound Sonography of bone density is available for the clinical measurement of individually developed osteoneogenesis by PRF.Conclusion: The multiplex analysis of PRF shows a dynamic and cytokine-based interaction with osteoneogenesis that is not yet fully clarified. Keywords: platelet-rich fibrin, multiplex analysis, cytokines, bone marrow defects of the jaw, osteoneogenesis, enoral transalveolar ultrasonograph